Peran Sistem Informasi dalam Pengembangan Pariwisata Berbasis Smart tourism di Tangerang Raya - Agus Sulaksono; Tommy Kuncara (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2026)
Tourism is a strategic sector that requires integrated information systems to improve service quality and tourist experience. Greater Tangerang has diverse tourism potential, including destinations, culinary attractions, landmarks, and events; however, its tourism information and services remain fragmented and do not yet support integrated trip planning. This study aims to design an integrated tourism website interface based on the Smart tourism concept for the Greater Tangerang area. The study employed a User-Centered Design (UCD) approach combined with the prototype method. The research stages included identifying the context of use, identifying user needs, analyzing system requirements, designing the proposed solution, developing the prototype using Figma, and conducting iterative evaluation and design refinement. The results indicate that the proposed website design is able to integrate information on tourist destinations, culinary attractions, landmarks, events, route planning, transportation ticket booking, hotel reservations, and dining options into a single digital platform. The designed system structure supports service integration, while the interface prototype demonstrates simple navigation flow, structured information presentation, and interconnected service features. This study contributes by providing an integrated tourism information system design as a basis for the development of Smart tourism services at the regional level.